Case Study of Individual with Paranoid Schizophrenia in X Mental Hospital - Anak Agung Ayu Bintang Kesuma Dewi; Yohana Wuri Satwika (Department of Psychology, Faculty of Education, Universitas Negeri Surabaya, 2024)
-